Waves in nonlinear layered metamaterials, gyrotropic and plasma media - Rapoport, Yuriy; Grimalsky, Vladimir (IOP (Series). Release 22., 2022)
The purpose is to give a wide, tutorial-driven, presentation of the theory of wave processes occurring in layered nonlinear metamaterials (MMs), gyrotropic and plasma media.